A Commentary on the Relationship between Globalization and Democracy - Spourdalakis, Michalis (Études helléniques / Hellenic Studies, 2008)
Globalization has become a buzzword. Democracy on the other hand is simply assumed. What I would like to do in this paper is to bring the two together and see how the former influences the latter. Of course, one does not have to be an expert to see that this is an enormously complex issue which cannot be dealt with exhaustively within the constraints of a brief article. However, it is only reasonable to claim that an outline of some dimensions of the relationship between globalization and democracy is possible. Nevertheless, I will try to do from the perspective of cosmopolitan citizen who is concerned about the future of democracy.